Evaluation of organochlorinated pesticide residue in the water of Ba Tri agricultural canal Ben Tre province - Dung, Nguyen Thi; Kim Phuong, Nguyen Thi (Vietnam Journal of Chemistry, 2014)
The residues of Organochlorine pesticides from the water of the agricultural canal and river in Ba Tri district, BenTre province were determined by gas chromatography with electron- capture detector. The solid phase extraction (SPE- C18) cartridge was applied to extract organochlorine pesticides residues in water samples. The samples were collected during the dry, wet season and the crop growing 2006-2007. The results showed that most of water samples were contaminated with pesticide at concentration from 0.01 to 2.00 ppb. The residue of pesticides in water mainly depended on the crops season and have highest value in the beginning of growing period. The concentration of pesticides residues decreased from rice- field to canal and river. There were many forbidden pesticide such as HCH, Endosulfan, Heptachlor, Dieldrin etc. have been found with high frequency in water. It causes a big risk for human heath and aquatic biota.